Alternative Or Smart Waste Management (Global Experiences And Cooperation): Establishing A Database, Spatial Information, And Projects To Improve Waste Collection Systems - Trifa Mohamed , Sayah Fatima , Derbal Soumeia , Hamlili Ismail (Migration Letters, 2024)
Alternative or smart waste management is a sustainable approach aimed at protecting the environment and improving public health. This approach can be achieved by applying global expertise and cooperation between countries and peoples, and by establishing a database, spatial information, and projects to improve waste collection systems. Dubai relies on alternative waste management, aiming to reduce the amount of waste sent to landfills. This management includes a set of actions, such as recycling, converting waste to energy, and reducing waste. Dubai has made significant progress in the field of alternative waste management, reducing the amount of waste sent to landfills from 90% in 2000 to 55% in 2023. Dubai aims to reach 75% by 2025.